(untitled) (Perner’s Contacts, 2012)
The emissions from the aircraft are split between CO2, non-CO2 gases and aerosols. CO2 is a well-known long-lived greenhouse gas. The other emissions consist mainly of NOx, water vapour, unburned hydrocarbons, sulphates and black carbon. The cruise altitude of present jet aircraft is approximately 9-13 km. Globally the largest proportion of emissions are released in this altitude range containing the upper troposphere and lower stratosphere. The geographical pattern of aircraft emissions reflects the structure of global scheduled air traffic. Emission maxima are found over North America, Europe, the North Atlantic flight corridor, Southeast Asia and the Far East. The largest amounts of emissions are released in the northern hemisphere. The impact of emissions of chemical compounds by aircraft engines can be seen in context of the chemical processes occurring in the natural troposphere and stratosphere. The changes in atmospheric chemistry due to aircraft emissions are investigated by usage of numerical models, for example atmospheric chemistry transport models and chemistry – climate models.